A Collaborative Approach to Patient Care: Insights from Laboratory, Pharmacy, and OR Teams - Nabeel Ateeq Alsubhi,; Anwar Hamed Alsubhi,; Bander Awad Alsubhi,; Fahad Matiq Alsubhi,; Mohammed Olayan Alsubhi,; Raoyah Ahmad Ibrahim Alsobhi,; Ahmed Eid Obaid Alsubhi,; Majed Morshed Alsobhi,; Akram Saoaileh Alsubhi,; Ahmed Ibrahim Humaid Alsubhi,; Sara Ahmad Ebrahim Alsubhi,; Abdulrahman Awad Faraj Alsubhi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: The modern healthcare has become highly multifaceted and requires the interaction of various specialists to provide the best results for patients. Healthcare teams in laboratories, pharmacies, and operating rooms (ORs) play defining roles in diagnoses, treatments, and surgeries; therefore, cooperation with other departments is crucial. It also makes the care that is delivered safe, and one that is grounded in evidence and incorporates all aspects of the patient’s requirements. Aim of work: To explore the collaborative dynamics among laboratory professionals, pharmacists, and OR teams, emphasizing how these partnerships enhance patient outcomes. Methods: We conducted a comprehensive search in the MEDLINE database's electronic literature using the following search terms: Collaborative, Approach, Patient Care, Laboratory, Pharmacy, and OR Teams. The search was restricted to publications from 2016to 2024 in order to locate relevant content. We performed a search on Google Scholar to locate and examine academic papers that pertain to my subject matter. The selection of articles was impacted by certain criteria for inclusion. Results: The publications analyzed in this study encompassed from 2016 to 2024. The study was structured into various sections with specific headings in the discussion section. Conclusion: Introducing and embracing a true multidisciplinary team approach focusing on patient and specifically laboratory, pharmacy, and OR teams is paramount to having the most positive outcomes possible. Some of the approaches that are recommended here include inter professional training, use of structured communication, use of information technology, definition of clear roles, and inter professional leadership support. Such practices facilitate sharing of information with any interested party; minimize the possibility of mistakes hence helping to improve patient safety and satisfaction. The kind of chemistry that is established in a healthcare organization team setting is very important because patients can receive more coordinated and quality care from staff.